Крайові задачі для диференціальних рівнянь, що не розв'язані відносно похідної, у просторі обмежених числових послідовностей - Самойленко, А.М.; Теплінський, Ю.В.; Недокіс, В.А. (Нелінійні коливання, 2007)
Исследуется нелинейная счетноточечная краевая задача для дифференциального уравнения,
не разрешенного относительно производной, которое вместе с нелинейным краевым условием
определено в банаховом пространстве ограниченных числовых последовательностей. Рассмотрена возможность редукции поставленной задачи к многоточечной краевой задаче в конечномерном пространстве. We study a nonlinear countable-point boundary-value problem for a differential equation that is not solved
with respect to the derivative. Both the equation and the nonlinear boundary condition are defined in the
Banach space of bounded number sequences. We also consider a possibility of reducing the posed problem
to a multiple-point boundary-value problem in a finite-dimensional space.